Does chronobiological preference affect the clinical appearance of obsessive-compulsive disorders - SAKALLI KANİ, AYŞE; TOPÇUOĞLU, VOLKAN; SAYAR, MUSTAFA KEMAL (My University, 2023)
Objective: There is a growing body of evidence support-ing the involvement of circadian rhythm abnormalities in the psychopathology of obsessive-compulsive disorder. However, the effects of chronotype preference on the clinical features of this disorder are elusive. The aim of this study is to investigate how chronobiological predis-positions of people with obsessive compulsive disorder affect obsessive compulsive disorder symptomatology, age of onset, course of the disease and accompanying comorbid conditions. Method: Within this cross-section-al study, 76 participants with mean age of 32.53, who have been under treatment with a diagnosis of obses-sive-compulsive disorder, were evaluated. Sociodemographic and clinical data form, Yale-Brown Obsessive Compulsive Scale, Morningness and Eveningness Questionnaire, Hamilton Depression Rating Scale, and Hamilton Anxiety Scale were applied to the participants. Results: 65.8% (n=50) of the participants consisted of women. Mean age of onset is 18.74 +/- 9.36 years. Most of the patients were reactive type (n=47, 61,8 %). Most common obsession type was contamina-tion (n=53, %69,74), the most common compulsion type was cleaning/washing (n=52, %68,42). There was no significant correlation between morningness and eveningness scale scores and obsession and compulsion types. No significant correlation was found between morningness and eveningness scale scores and OCD onset age. There was no significant difference between morningness and eveningness scale scores according to the OCD type of the patients and the presence of accom-panying clinical diagnoses. Discussion: Morningness or eveningness chronotype tendencies did not have a sig-nificant impact on the clinical appearance of OCD.

Amaç: Obsesif kompulsif bozukluğun psikopatolojisinde sirkadiyen ritim anormalliklerinin rol oynadığını destekleyen kanıtlar giderek artmaktadır. Ancak kişilerin kronotip farklılıklarının bu bozukluğun klinik özelliklerini nasıl etkilediği henüz bilinmemektedir. Bu çalışmanın amacı, obsesif kompulsif bozukluk tanısı olan bireylerdeki kronotip farklılıklarının obsesif kompulsif bozukluk semptomatolojisi, hastalığın ortaya çıkış yaşı, klinik seyri ve eşlik eden komorbid durumları etkileyip etkilemediğini araştırmaktır. Yöntem: Bu çalışmada obsesif kompulsif bozukluk tanısı ile tedavi gören yaş ortalaması 32,53 olan 76 katılımcı değerlendirilmiştir. Katılımcılara sosyodemografik ve klinik veri formu, Yale-Brown Obsesyon Kompulsiyon Ölçeği, Sabahlılık ve Akşamlılık Ölçeği, Hamilton Depresyon Derecelendirme Ölçeği ve Hamilton Anksiyete Ölçeği uygulanmıştır. Bulgular: Katılımcıların %65,8'i (n=50) kadınlardan oluşmaktadır. Ortalama başlangıç yaşı 18.74 ± 9.36 yıldır. Hastaların çoğu reaktif tiptir (n= 47, %61,8). En sık obsesyon tipi kontaminasyon (n=53, %69,74), en yaygın kompulsiyon tipi temizlik/yıkama (n=52, %68,42) olarak saptanmıştır. Sabahlılık ve akşamlılık ölçeği puanları ile obsesyon ve kompulsiyon tipleri arasında anlamlı bir korelasyon yoktur. Sabahlılık ve akşamlılık ölçeği puanları ile OKB başlangıç yaşı arasında herhangi anlamlı bir korelasyon saptanmamıştır. Hastaların OKB tipi ve eşlik eden klinik tanıların varlığına göre sabahlılık ve akşamlılık ölçeği skorları arasında anlamlı bir farklılık yoktur. Sonuç: Obsesif kompulsif bozukluk tanısı olan bireylerde, sabahlılık ve akşamlılık kronotip eğilimlerinin hastalığın klinik görünümü üzerinde anlamlı bir etkisi olmadığı gözlenmiştir.
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Psychiatry and Mental Health; chronotype; obsession compulsion type; clinical features; PSYCHOTROPIC MEDICATIONS; SYMPTOM; SUICIDALITY; CHRONOTYPE; DIMENSIONS; ANALOG; SCALE; chronotype; obsession compulsion type; clinical features; kronotip; obsesyon kompulsiyon tipi; klinik özellikler